SiAlS (Simple Alarm System) Based Light Dependent Resistor (LDR) and Basic Logic Gate as an Attempt to Preventing on Helmet Theft - Rahmadi, Aji; Dimisa, Adi Ahmad; Kurniawan, Asep; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Research on the Light Dependent Resistor (LDR) and the basic logic gates in the designing and manufacturing SiAlS (Simple Alarm System) as an attempt to Prevent theft helmet on had been done. This research was conducted aiming to create and Characterize alarm system. This study was intended to Prevent theft of the helmet. The method used in this research is divided into three stages, designing, manufacturing and testing. The working principle of this alarm system is when the helmet is mounted in the rearview mirror, the LDR will be closed so that the resistance increases the which causes the alarm to Become inactive. However, if the helmet is taken, the alarm will activate because The resistance decreases. However, the alarm will not work if the sensor cable is cut by the thief. To Overcome this problem, additional circuits are made using a NOT logic gates. The results of this research are prototypes in testing alarm systems and alarm systems get a 100% success rate. The advantage of this alarm systems are cheap and simple, Because it does not use a microcontroller and can be made individually.